Meditation for Migraines: A Pilot Randomized Controlled Trial. Issue 9 (18th July 2014) - Wells, Rebecca Erwin; Burch, Rebecca; Paulsen, Randall H.; Wayne, Peter M.; Houle, Timothy T.; Loder, Elizabeth
Abstract : Objective: Our objective was to assess the safety, feasibility, and effects of the standardized 8‐week mindfulness‐based stress reduction (MBSR) course in adults with migraines. Background: Stress is a well‐known trigger for headaches. Research supports the general benefits of mind/body interventions for migraines, but there are few rigorous studies supporting the use of specific standardized interventions. MBSR is a standardized 8‐week mind/body intervention that teaches mindfulness meditation/yoga. Preliminary research has shown MBSR to be effective for chronic pain syndromes, but it has not been evaluated for migraines. Methods: We conducted a randomized controlled trial with 19 episodic migraineurs randomized to either MBSR (n = 10) or usual care (n = 9). Our primary outcome was change in migraine frequency from baseline to initial follow‐up. Secondary outcomes included change in headache severity, duration, self‐efficacy, perceived stress, migraine‐related disability/impact, anxiety, depression, mindfulness, and quality of life from baseline to initial follow‐up. Results: MBSR was safe (no adverse events), with 0% dropout and excellent adherence (daily meditation average: 34 ± 11 minutes, range 16‐50 minutes/day). Median class attendance from 9 classes (including retreat day) was 8 (range [3, 9]); average class attendance was 6.7 ± 2.5. MBSR participants had 1.4 fewer migraines/month (MBSR: 3.5 to 1.0 vs control: 1.2 to 0 migraines/month, 95% confidence interval CI [−4.6, 1.8], P = .38), an effect that did not reach statistical significance in this pilot sample. Headaches were less severe, although not significantly so (−1.3 points/headache on 0‐10 scale, [−2.3, 0.09], P = .053) and shorter (−2.9 hours/headache, [−4.6, −0.02], P = .043) vs control. Migraine Disability Assessment and Headache Impact Test‐6 dropped in MBSR vs control (−12.6, [−22.0, −1.0], P = .017 and −4.8, [−11.0, −1.0], P = .043, respectively). Self‐efficacy and mindfulness improved in MBSR vs control (13.2 [1.0, 30.0], P = .035 and 13.1 [3.0, 26.0], P = .035 respectively). Conclusions: MBSR is safe and feasible for adults with migraines. Although the small sample size of this pilot trial did not provide power to detect statistically significant changes in migraine frequency or severity, secondary outcomes demonstrated this intervention had a beneficial effect on headache duration, disability, self‐efficacy, and mindfulness. Future studies with larger sample sizes are warranted to further evaluate this intervention for adults with migraines. This study was prospectively registered (ClinicalTrials.gov identifier NCT01545466).